2019
DOI: 10.1186/s13052-019-0717-8
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease triggered by EBV virus in a child with Familial Mediterranean Fever

Abstract: Background Familial Mediterranean Fever is a monogenic autoinflammatory disease, secondary to mutation of MEFV gene, and typically expressed with recurrent attacks of fever, serositis, rash, aphthous changes in lips and/or oral mucosa. Kawasaki Disease, an acute systemic vasculitis with persistent fever (5 or more days), rash, stomatitis, conjunctivitis, lymphadenopathy, changes in extremities, is currently considered a multifactorial autoinflammatory disease. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Multiple infectious triggers such as adenovirus and novel coronavirus have been inconclusively associated with KD (11,12). Also, KD has been associated with Epstein-Barr virus (EBV), rotavirus, and speci c bacteria (13,14). In this regard, WHO has also developed a preliminary case de nition and case report form for MIS in children and adolescents for approaching these diseases (15).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple infectious triggers such as adenovirus and novel coronavirus have been inconclusively associated with KD (11,12). Also, KD has been associated with Epstein-Barr virus (EBV), rotavirus, and speci c bacteria (13,14). In this regard, WHO has also developed a preliminary case de nition and case report form for MIS in children and adolescents for approaching these diseases (15).…”
Section: Discussionmentioning
confidence: 99%
“…41 A prospective study by Bajolle et al revealed that bocavirus was present in the serum of 3/32 (9%) and in the nasopharyngeal aspirate of 7/32 (21.8%) patients with KD, who probably had a previous bocavirus infection heralding KD. 42 Metagenomic sequencing and PCR detected torque teno virus 7 in only 2/11 (18%) patients with KD prospectively evaluated for one year, 43 while the most recent reports have highlighted the association of KD with Epstein-Barr virus, 44 parvovirus B19 45 and influenza virus. 46 The Outbreak of the New Coronavirus and Kawasaki Disease.…”
Section: A Systemic Vasculitis Is the Key To Explain Kawasakimentioning
confidence: 99%
“…Multiple infectious triggers such as adenovirus and New Haven coronavirus have been inconclusively associated with KD in the past [ 7 , 8 ]. Also, KD has been in associations with Epstein–Barr virus (EBV), rotavirus, and bacteria [ 9 , 10 ]. In this regard, the WHO has also developed a preliminary case definition and case report form for MIS in children and adolescents for approaching these diseases [ 2 ].…”
Section: Discussionmentioning
confidence: 99%